Night Market Appeal: How the Quality of Facilities, Food, and Program Content Shapes Visitor Satisfaction and Continuous Visiting Behavior - Stephanie Caroline; Retno Ardianti (International Journal of Entrepreneurship, Business, and Creative Economy, 2026)
Night markets have become prominent urban attractions across major Asian cities, serving not only as tourism hotspots but also as community spaces that support local entrepreneurship. Despite their role in enabling entrepreneurial activity and fostering vibrant visitor experiences, their long-term ability to continuously attract visitors remains unknown. Therefore, this study aims to identify key factors that affect visitors’ satisfaction and their continuous visiting behavior. More specifically, this study investigates the effect of the quality of facilities, food, and program content at the night market and their effects on visitor satisfaction and continuous visiting behavior. To achieve this aim, this study uses a quantitative approach, utilizing survey data from 184 visitors of a night market in Surabaya, Indonesia.  Using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the data, the findings reveal that high-quality facilities, diverse and appealing food, and well-organized program content have significant effects on visitor satisfaction and continuous visiting behavior. In doing so, this study extends the Expectation Confirmation Model by incorporating these specific attributes, highlighting the interplay of physical, sensory, and experiential factors to explain the behavior of night markets’ visitors. This research offers theoretical and empirical insights into consumer behavior in non-traditional tourism settings, addressing a gap in the literature on night markets as local attractions that contribute to the local economy. The practical implications provide actionable guidance for market organizers and entrepreneurs to enhance facilities, innovate food offerings, and design engaging programs that encourage visitors to return.